Classification and classification criteria for vasculitis: achievements, limitations and prospects. Issue 1 (January 2015) - Mahr, Alfred; de Menthon, Mathilde
Abstract : Purpose of review: The classification of diseases reveals the relationships between conditions that are linked in some way. Such classification has been a challenge for vasculitis because of the heterogeneous and protean nature of the illnesses. Classification criteria are critical to homogenize patient populations with vasculitis who are included in basic and clinical research studies. Recent findings: The most recent advance in vasculitis classification has been the revised 2012 Chapel Hill Consensus Conference (CHCC) nomenclature of vasculitis that, although mainly focusing on nomenclature, also included classification elements. Whereas still maintaining the caliber of the predominantly involved vessels as the main categorization criterion for primary systemic vasculitis, the 2012 CHCC nomenclature introduced a new category – variable-vessel vasculitis – to include Behçet's disease and Cogan's syndrome in the vasculitis spectrum. Another important feature was the expansion of the classification to secondary vasculitis and single-organ vasculitis. Similarly, classification criteria for several vasculitis entities have been altered and new criteria published, namely for Behçet's disease and cryoglobulinemic vasculitis. Summary: The classification of vasculitis continues to be amended to account for advances in the general understanding of the nature of vasculitis and our ability to diagnose them. The relevance of the prevailing classification system, relying on affected vessel size as the primary discriminator of vasculitis entities, is still questionable for clinical practice. Clinically sound, widely accepted classification criteria are available for most vasculitis entities, although some areas remain ill-defined: polyarteritis nodosa, microscopic polyangiitis and adult immunoglobulin A vasculitis (Henoch–Schönlein).